Tissue analysis by vibrational spectroscopy in Hirschsprung disease: feasibility and potential as a new intraoperative tool - Combescot, C; Piot, O; Untereiner, V; Durlach, A; Laconi, F (Analyst (London), 2025)
Hirschsprung disease is a congenital anomaly characterised by an absence of innervation in the colon. The current diagnosis, which involves identifying the non-functional part of the colon through histological examination, is unsatisfactory. The objective of our study was to assess the potential of infrared spectroscopy as a label-free method to distinguish between functional and non-functional parts of the colon. Tissue samples from FFPE sections of Hirschsprung patients, taken from both functional and non-functional regions, were analysed by mid-infrared imaging. Colour-coded spectral images, reconstructed using multivariate data processing, were compared to the gold standard (hematoxylin-eosin-safran staining) to associate a specific spectral signature with each histological structure. Statistical analyses were also carried out to highlight infrared markers associated with Hirschsprung disease. The search for ganglion cells and cholinergic threads, the usual markers of the disease, was unsuccessful. However, our approach was efficient in differentiating between functional and non-functional parts of the colon by focussing on the muscularis. As such, vibrational spectroscopy can highlight biochemical differences that are not visible using standard histology. This proof-of-concept study suggests that vibrational spectroscopy is a candidate method for diagnosing Hirschsprung disease, paving the way for intraoperative application by assisting surgeons and histologists in delineating the pathological region.